Findings of the Association for Computational Linguistics: EMNLP 2020 2020
DOI: 10.18653/v1/2020.findings-emnlp.15
|View full text |Cite
|
Sign up to set email alerts
|

Converting the Point of View of Messages Spoken to Virtual Assistants

Abstract: Virtual Assistants can be quite literal at times. If a user says tell Bob I love him, most virtual assistants will extract the message I love him and send it to the user's contact named Bob, rather than properly converting the message to I love you. We designed a system that takes a voice message from one user, converts the point of view of the message, and then delivers the result to its target user. We developed a rulebased model, which integrates a linear text classification model, part-of-speech tagging, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In fact, the English grammar is mostly descriptive rather than prescriptive -no set of official rules dictated by a single governing authority exists. Even so, rule based POV conversion does provide a strong baseline compared to state-of-the-art techniques, such as end-to-end Transformer networks (Lee et al, 2020). In this study, we limit our scope to rule-based conversion because only the rule-based system among all tested methods in Lee et al (2020) confers to the unsupervised nature of this paper.…”
Section: Pov Conversionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the English grammar is mostly descriptive rather than prescriptive -no set of official rules dictated by a single governing authority exists. Even so, rule based POV conversion does provide a strong baseline compared to state-of-the-art techniques, such as end-to-end Transformer networks (Lee et al, 2020). In this study, we limit our scope to rule-based conversion because only the rule-based system among all tested methods in Lee et al (2020) confers to the unsupervised nature of this paper.…”
Section: Pov Conversionmentioning
confidence: 99%
“…Even so, rule based POV conversion does provide a strong baseline compared to state-of-the-art techniques, such as end-to-end Transformer networks (Lee et al, 2020). In this study, we limit our scope to rule-based conversion because only the rule-based system among all tested methods in Lee et al (2020) confers to the unsupervised nature of this paper. We encourage further research into integrating more advanced reported speech conversion techniques into the abstractive summarization pipeline.…”
Section: Pov Conversionmentioning
confidence: 99%
See 2 more Smart Citations